Pengaruh Fenomena PHK Serentak Terhadap Persepsi Karir & Hubungan Interpersonal Melalui Adaptasi Karir pada Generasi Z Kab. Garut - Muhammad Ramdhan; Oktri Mohammad Firdaus; Irfan Rizki Gumilar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The recent wave of simultaneous layoffs has posed a serious challenge to the career stability of young workers, particularly Generation Z who are at an early stage of entering the workforce. This situation creates uncertainty that may influence individuals’ career perceptions as well as the quality of their interpersonal relationships, both in workplace and social settings. This study aims to examine the effects of simultaneous layoffs on career perception and interpersonal relationships, with career adaptability serving as a mediating variable among Generation Z in Garut Regency. This research adopts a quantitative approach using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to Generation Z individuals in Garut Regency who were affected by or at risk of being affected by layoffs, using a purposive sampling technique. Data analysis involved the evaluation of both the measurement and structural models to assess direct and indirect relationships among the research variables. The findings indicate that simultaneous layoffs have a significant effect on career perception and interpersonal relationships. Moreover, career adaptability is found to play a mediating role in helping Generation Z cope with the impact of layoffs, such that individuals with higher levels of career adaptability tend to exhibit more positive career perceptions and more harmonious interpersonal relationships. This study is expected to contribute both academically and practically to policy formulation and career development programs aimed at enhancing career adaptability among Generation Z at the regional level.